PENGARUH PENGGUNAAN MEDIA QUIZIZZ PAPER MODE TERHADAP KEMAMPUAN BERPIKIR KRITIS PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV DI SEKOLAH DASAR - Aura Fitria Ananda; Dayu Rika Perdana; Agung Dian Putra; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low critical thinking skills of students and the suboptimal use of media in learning Pancasila Education for fourth-grade students at SD Negeri Rejomulyo. This research aims to determine the effect of using Quizizz Paper Mode media on students' critical thinking skills in Pancasila Education. The research method employed a quasi-experimental design with a non-equivalent control group. The population consisted of 52 students, with a sample of 28 students from class IVA as the experimental group and 24 students from class IVB as the control group. The sample was selected using non-probability saturated sampling, where the entire population was used as the sample. Data collection techniques included tests, observation, and documentation. Data analysis used a simple linear regression test, which showed. The results indicate a significant effect of using Quizizz Paper Mode media on the critical thinking skills of fourth-grade students in Pancasila Education at SD Negeri Rejomulyo.